EXPLORING THE IMPACT OF DIFFERENTIATED INSTRUCTION ON STUDENTS’ PERCEPTION, ENGAGEMENT, MOTIVATION IN EFL HIGH SCHOOL EDUCATION - Saputri, Like Ayu; Anwar, Khoirul; Maruf, Nirwanto (Universitas PGRI Sumatera Barat, 2023)
This study investigates the impact of Differentiated Instruction (DI) in high school English as a Foreign Language (EFL) education, analyzing its influence on students' perceptions, motivation, and engagement. Using mixed methods, it delivers a comprehensive assessment of DI's effectiveness. Quantitative analysis of survey data reveals a strong, positive perception of DI among EFL high school students. Each one-unit increase in students' DI perception corresponds to a 0.508 units increase in DI (t = 10.613, p < 0.001, Beta = 0.639). Engagement also significantly impacts DI; a one-unit increase in engagement yields a 0.496 units increase in DI (t = 10.512, p < 0.001, Beta = 0.653). Conversely, motivation negatively relates to DI; a one-unit increase in motivation results in a 0.353 units decrease in DI (t = -7.219, p < 0.001, Beta = -0.305). Qualitative insights from in-depth interviews resonate with the quantitative findings. Students express heightened engagement, enjoyment, and empowerment through DI, accompanied by a positive shift in their perspectives. They credit DI with accommodating diverse readiness levels, enhancing learning achievements, and reshaping their views of English as a subject. Additionally, the flexible grouping strategies within DI foster dynamic, collaborative learning environments. In sum, this research highlights the multifaceted benefits of DI in EFL high school education, offering a nuanced understanding of its implications within this context. This abstract has been expanded to 240 words to provide a more comprehensive overview of the study's findings and implications.